In‐hospital outcomes of transesophageal versus intracardiac echocardiography guided left atrial appendage closure. Issue 5 (23rd January 2022) - Morcos, Ramez; Megaly, Michael; Saad, Marwan; Barakat, Amr F.; Rubens, Muni; Saxena, Anshul; Elbadawi, Ayman; Kucharik, Michael; Luna, Michael; Garcia, Santiago; Veledar, Emir; Maini, Brijeshwar; et al.
Abstract: Background: Transesophageal echocardiogram (TEE) is the preferred imaging modality to guide transcatheter left atrial appendage closure (LAAC). Intracardiac echocardiography (ICE) has evolved as a less invasive alternative to TEE. Several observational studies have shown similar success rates and perioperative complications between TEE and ICE for LAAC. Objectives: We sought to examine the temporal trends and patient characteristics of TEE versus ICE use in LAAC using a national database. We also evaluated hospital outcomes including periprocedural complications, mortality, and length of hospital stay. Methods: This is a retrospective analysis of data from the National Readmission Database, collected from 2016 to 2018. The primary outcome was major adverse events (MAE) defined as in‐hospital mortality, cardiac arrest, pericardial effusion with or without tamponade, pericardiocentesis or window pericardiocentesis and pericardial window, pericardial effusion and tamponade, and hemorrhage requiring transfusion. Results: Trend analysis showed that TEE‐guided LAAC increased from 96.6% in 2016 to 98.4% in 2018 (relative increase, 1.9%), while ICE‐guided LAAC decreased from 3.4% to 1.6% during the same period (relative decrease, 53%, p for trend = 0.08). In the unmatched cohorts, the MAE was significantly lower in TEE‐guided LAAC compared to ICE‐guided LAAC (6.5% vs. 9.3%, p = 0.022). In the propensity score matching analysis, MAE remained significant (5.6% vs. 9.4%, p < 0.001). The incidence of pericardial effusion with or without tamponade remained significantly lower in the TEE group (2.3% vs. 5.8%, p < 0.001). Length of stay (3.4 vs. 1.9 days, p < 0.001) and hospitalization cost (34, 826 vs. 20, 563, p < 0.001) remained significantly lower for TEE‐guided LAAC. Conclusions: Compared to ICE, the incidence of MAE was significantly lower for TEE‐guided LAAC, driven mainly by less pericardial effusion events. Large‐scale randomized trials are needed to confirm the findings of the current and previous studies.